Design and Implementation of a Portable ECG Device - Bhattarai, Sulove; Bhujel, Sudip; Adhikari, Santosh; Maharjan, Shanta (Journal of Innovations in Engineering Education, 2020)
Electrocardiography(ECG) is the technology of measuring the electrical changes of the heart. The electrical change is due to the depolarization and repolarization of the heart cells which produces a specific wave or complex. The potential developed is captured by the electrodes placed on the skin, which ranges in micro to millivolts. Weak signals captured by the electrodes are amplified and converted into a voltage that is readable for microcontroller ATmega328P. ECG is represented by the waves called P, QRS, and T waves. One cardiac cycle of the heart consists of P-QRS-T waves in ECG. The amplitude of the waves, complexes, and the time interval between different waves or segments conveys the total information on the working activity of the heart. A proper study of those waveforms and time intervals on ECG aids to determine and diagnose different cardiac abnormalities. This paper presents a method of extraction of voltage generated during cardiac movement of the human body using an electrode, amplifier, microcontroller and OLED screen. It describes the method of calculating heartbeats per minute from the ECG signal and displays beats per minute on the same OLED screen.